Marketing Strategy to Increase Sales Volume: A SWOT-Based Analysis of a Sharia Multilevel Marketing Health Product Distributor - Siti Amirah Makarim; Sani Haryati; Lati Sari Dewi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines marketing strategies employed by a Sharia-based multilevel marketing health product distributor in Kendari to enhance sales performance. A descriptive qualitative methodology was applied, incorporating SWOT analysis through Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) matrices. Data were gathered via interviews, direct observation, structured questionnaires, and document review. Findings reveal that the distributor experienced a notable downturn in sales at the beginning of the observed period, despite operating in a market characterized by heightened health awareness during the COVID-19 pandemic. SWOT analysis identified internal strengths, particularly halal-certified products and a committed agent network, alongside weaknesses related to limited digital marketing adoption. External analysis highlighted growing consumer health consciousness as a key opportunity, while intensifying competition among Sharia-certified MLM companies posed the primary threat.